2014
DOI: 10.3928/01477447-20140225-52
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nail Prominence and Insertion Point on Anterior Knee Pain After Tibial Intramedullary Nailing

Abstract: Chronic anterior knee pain is the most common complication after tibial nail insertion. Its etiology remains unknown, and multifactorial sources have been suggested. The authors believe that nail prominence and the insertion point of the nail are important in the development of anterior knee pain. The purpose of this retrospective study was to evaluate the roles of the insertion point and nail prominence in anterior knee pain after tibial intramedullary nailing using a transtendinous approach and a common nail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Etiologies may include iatrogenic damage to the IP nerve, 42 to Hoffa's fat pad, 44 periosteal irritation of the entry point, patellar tendinopathy, or nail prominence. 45 Moreover, knee pain persists after nail removal in up to 60% of the cases. 5 , 42 , 46 It may be noteworthy that the IP-approach is used for implant removal, even after initial SP-nailing.…”
Section: Discussionmentioning
confidence: 99%
“…Etiologies may include iatrogenic damage to the IP nerve, 42 to Hoffa's fat pad, 44 periosteal irritation of the entry point, patellar tendinopathy, or nail prominence. 45 Moreover, knee pain persists after nail removal in up to 60% of the cases. 5 , 42 , 46 It may be noteworthy that the IP-approach is used for implant removal, even after initial SP-nailing.…”
Section: Discussionmentioning
confidence: 99%
“…Boerger et al investigated the outcome of 100 nail removals, and reported that intramedullary nail removal is a safe procedure, but anterior knee pain may persist in a significant proportion of patients after nail removal [ 10 ]. There are few reports in the literature of the complications associated with the removal of intramedullary nails [ [9] , [10] , [11] , [12] ]. Depending on study design and composition and position of nails, nail removal may cause various problems and the operating time, amount of bleeding, and difficulty of removal can vary accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…1 They highlight the important conclusion that the cause of anterior knee pain following tibial intramedullary nailing remains unknown, with multifactorial sources having been reported.…”
Section: Replymentioning
confidence: 99%
“…1 The source of anterior knee pain following tibial intramedullary nailing remains unknown and is most likely multifactorial. 1,2 We believe that having 2 groups of patients with homogeneous characteristics minimizes the effects of multiple causes of anterior knee pain.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation